Mesoscale Mechanism of P‐dopant Defects and Interface Synergy for Phenols Degradation. Issue 16 (12th July 2022) - Zhang, Kaiqi; Song, Hongyan; An, Zhe; Zhang, Jian; Zhu, Yanru; Chai, Zhigang; Shu, Xin; He, Jing
Abstract: The semiconductor based photocatalysis has become a hot spot of current research, and the key challenges are the construction of strong functional heterojunction photocatalysts, and insights on the working mechanism involved. In this work, we constructed a NiFe‐ LDHs/P‐TCN heterojunction with P‐dopant defects and interface synergy and elucidated its mesoscale mechanism among different constituent interfaces. The interface photoelectron transfer was detected by PAS, EPR and other methods, and the enhancing mechanism of the defect sites for interface electron transfer and photocatalytic activity was proposed. The interfacial electrons, photoelectric properties and photocatalytic activity are found to be positively correlated. The result is conducive for a better understanding on working mechanism of heterogeneous photocatalysts, which opened a broader research space for the rational design and construction of functional interfaces. Abstract : NiFe‐ LDHs/P‐TCN heterojunction has been constructed with P‐dopant defects and interface synergy. Moreover, Its mesoscale mechanism was elucidated among different constituent interfaces.